2017
DOI: 10.1007/s00213-017-4542-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on response inhibition and interference control

Abstract: Nicotine is a cholinergic agonist with known pro-cognitive effects in the domains of alerting and orienting attention. However, its effects on attentional top-down functions such as response inhibition and interference control are less well characterised. Here, we investigated the effects of 7 mg transdermal nicotine on performance on a battery of response inhibition and interference control tasks. A sample of N = 44 healthy adult non-smokers performed antisaccade, stop signal, Stroop, go/no-go, flanker, shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 94 publications
(126 reference statements)
5
22
0
Order By: Relevance
“…Rather than a blanket inability to engage cognitive and attentional resources, the deficit appears specific to conditions where only relatively minimal attention is required. The robust effects 14 on attention that we report are in line with literature on attention-enhancing effects of nicotine 14,41 and problems with sustained attention in smokers [42][43][44][45] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Rather than a blanket inability to engage cognitive and attentional resources, the deficit appears specific to conditions where only relatively minimal attention is required. The robust effects 14 on attention that we report are in line with literature on attention-enhancing effects of nicotine 14,41 and problems with sustained attention in smokers [42][43][44][45] .…”
Section: Discussionsupporting
confidence: 90%
“…Some studies report worse cognitive control performance in smokers 30,31,47 , while others did not 33,48,49 . Studies manipulating satiety within-subject similarly reported mixed results for cognitive control tasks 42,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Separate ANCOVAS were performed on reaction time data, errors of commission, and errors of omission using current nicotine, current marijuana, and prenatal alcohol as covariates, which were selected given that these variables have been shown to impact performance on inhibitory responding tasks, such as the Go/No-Go (Burden et al, 2010;Ettinger et al, 2017;Hatchard et al, 2015;Luijten, Little, & Franken, 2011;Smith et al, 2011;Wrege et al, 2014;Zhao et al, 2016). Other variables that have been shown to impact response inhibition, like age and education, did not warrant inclusion as covariates in the analyses, as there was little variability on these measures between groups (in terms of standard errors), while the selected drug exposure covariates did show variability between groups.…”
Section: Performance Parameters and Analysesmentioning
confidence: 99%
“…While the effects of nicotine on antisaccades have been investigated previously (2534; 67; 68), to our knowledge, this is the first antisaccade study applying a more general pro-cholinergic drug (as an AChE inhibitor, galantamine raises ACh levels in general). Our findings replicate previous studies in which nicotine was found to reduce antisaccade RT (25; 27; 28; 30; 33).…”
Section: Discussionmentioning
confidence: 95%